12. STUDY ON THE RELATIONSHIP BETWEEN CORONARY ARTERY CALCIFICATION LEVEL AND THE RISK OF ACUTE CORONARY SYNDROME RECURRENCE AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to examine the characteristics of coronary artery calcification and evaluate the relationship between the level of calcification and the risk of acute coronary syndrome (ACS) recurrence after intervention at Thong Nhat Hospital.Subjects and Methods: A cross-sectional descriptive study was conducted from January to June 2025 on 272 patients diagnosed with acute coronary syndrome who had calcified lesions identified by angiography and optical coherence tomography. Data collected included demographic characteristics, cardiovascular risk factors, calcification features, and intervention techniques. Data were analyzed using SPSS 26.0 with a significance level of p < 0.05.Results: 57% of patients had calcified plaques; among them, 33.2% had diffuse calcification and 20.6% had nodular calcification protruding into the vessel. Special techniques like cutting balloons and rotablation were used in 24.3% and 16.2% of cases, respectively. The rate of optimal stent expansion was 90.4%, and the overall procedural success rate was 94.1%.Conclusion: The study showed that complex calcified lesions increased intervention difficulty and recurrence risk. Accurate assessment of calcification and selection of appropriate techniques are key to improving treatment outcomes and reducing complications.
Keywords: Coronary artery calcification, acute coronary syndrome, percutaneous coronary intervention.